2020
DOI: 10.1097/gox.0000000000003200
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Plastic Surgery: Current Applications, Future Directions, and Ethical Implications

Abstract: Background: Artificial intelligence (AI) in healthcare delivery has become an important area of research due to the rapid progression of technology, which has allowed the growth of many processes historically reliant upon human input. AI has become particularly important in plastic surgery in a variety of settings. This article highlights current applications of AI in plastic surgery and discusses future implications. We further detail ethical issues that may arise in the implementation of AI in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…Current smartphone technology should not supplant the shared decision-making process between patient and provider, but rather augment it. 32 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current smartphone technology should not supplant the shared decision-making process between patient and provider, but rather augment it. 32 34 …”
Section: Discussionmentioning
confidence: 99%
“…Current smartphone technology should not supplant the shared decision-making process between patient and provider, but rather augment it. [32][33][34] As mobile applications for patient care evolve, so should patient data safety measures. Of the eight applications with the potential to handle patient data, seven demonstrated some degree of data safety measures (Table 2).…”
Section: Data and Ethical Considerationsmentioning
confidence: 99%
“…This is the first systematic review focusing on the application of ML in plastic surgery, adding to previous reviews on AI in the specialty. 72 After careful selection of studies that demonstrated the clinical application of these algorithms, we identified 51 articles describing the application of 103 ML algorithms. In our review, the mean accuracy for diagnosis prediction, outcome prediction, and preoperative planning was 88.80%, 86.11%, and 80.28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…AIenabled decision-making tools combined with predictive analytics and integrating human surgical intuition hold great promise for improving surgical outcomes. The surgeon could make real-time decisions perioperatively based on 3D planning, anatomical localization, and surgical navigation [15,18,21,26]. Complex surgical procedures cannot be performed with current AI tools.…”
Section: Future Applicationsmentioning
confidence: 99%